Nursing interventions on oral anticoagulation therapy: An integrative review (Research, Society and Development, 2023)
Introduction: Oral anticoagulant therapy is a complex therapeutic scheme for the prevention of thromboembolic events. Currently, with all the demands for improved quality of care and cost reduction in the current research development demand, it makes necessary multiprofessional interventions with educational components to assist in the management of the treatment. Within the scope of nursing contribution, the use of standardized language can help nurses of different contexts and nationalities to act supported by evidence. Objectives: To identify health interventions in therapy in the literature and stratify them according to the level of evidence, and to map nursing actions found in the literature to the interventions/activities proposed by the Nursing Interventions Classification. Methods: This is an integrative review study, followed by a cross-mapping through the Virtual Health Library, which will bring papers from IBECS, LILACS, BDENF and MEDLINE. To carry out the cross-mapping we used the adapted rules, based on Lucena and Barros (2005). Results: Sixteen papers were selected according to the PRISMA flowchart, with sociodemographic data and level of evidence. The interventions for adherence were grouped into groups of: education, self-management and directly observed treatment, with the mapping performed according to the Nursing Interventions Classification. Conclusion: The interventions include educational issues, self-management and directly observed treatment to promote patient adherence within the therapy, for this the evidence points to treatment in specialized centers which then spend yours resources in m-health, pill boxes, audio visual resources, primers, consultations focused on the particularities of the patient.